2021
DOI: 10.3390/foods10050937
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidants: Innovative Extraction and Application in Foods

Abstract: Research has devoted great attention to the study of the biological properties of plants, animal products, microorganisms, marine species, and fungi, among others, often driven by the need to discover new medicines [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, it can also further improve the resolution of unknown compounds, especially for poor chromatographic separation. The antioxidant capacity of foods plays an important role in the diet, which is related to anticancer and anti-aging effects, improvement in immune function, and the prevention of cardiovascular diseases and nervous system diseases [ 16 ]. Previous studies have indicated that MSCP had strong antioxidant activity [ 17 ] and anti-fatigue activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it can also further improve the resolution of unknown compounds, especially for poor chromatographic separation. The antioxidant capacity of foods plays an important role in the diet, which is related to anticancer and anti-aging effects, improvement in immune function, and the prevention of cardiovascular diseases and nervous system diseases [ 16 ]. Previous studies have indicated that MSCP had strong antioxidant activity [ 17 ] and anti-fatigue activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants can be found in vegetables, fruits, cereals, most medicinal herbs, nuts, some meats, poultry, and fish (Nemzer et al, 2019;Jideani et al, 2021). Antioxidants are found naturally in foods and improve human health without causing harm, as opposed to synthetic antioxidants (Loizzo and Silva, 2021). It is the most effective method of protecting the body from free radical damage in an emergency.…”
Section: Introductionmentioning
confidence: 99%